2016
DOI: 10.1007/164_2016_5003
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudomonas aeruginosa Exoenzyme Y: A Promiscuous Nucleotidyl Cyclase Edema Factor and Virulence Determinant

Abstract: Exoenzyme Y (ExoY) was identified as a component of the Pseudomonas aeruginosa type 3 secretion system secretome in 1998. It is a common contributor to the arsenal of type 3 secretion system effectors, as it is present in approximately 90% of Pseudomonas isolates. ExoY has adenylyl cyclase activity that is dependent upon its association with a host cell cofactor. However, recent evidence indicates that ExoY is not just an adenylyl cyclase; rather, it is a promiscuous cyclase capable of generating purine and py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 61 publications
(95 reference statements)
0
30
0
Order By: Relevance
“…The AC domain of CyaA belongs to the class II of adenylyl cyclase enzymes [EC 4.6.1.1] that convert ATP to cAMP, a “second messenger” and key intracellular signaling molecule [ 40 ]. The AC of CyaA of Bordetellae [ 5 , 8 ], the edema factor (EF) of Bacillus anthracis [ 41 , 42 ] and the ExoY effector of Pseudomonas aeruginosa [ 43 , 44 ] play an important role in virulence of these pathogenic bacteria. These AC enzymes exhibit a very low catalytic activity inside bacterial cytosol and are only activated upon delivery into cytosol of host eukaryotic cells, where ExoY is activated by filamentous actin [ 45 ], while the EF and the AC domain of CyaA are activated upon binding of eukaryotic CaM in a 1:1 stoichiometry [ 22 , 41 , 46 ].…”
Section: Cyaa Structurementioning
confidence: 99%
“…The AC domain of CyaA belongs to the class II of adenylyl cyclase enzymes [EC 4.6.1.1] that convert ATP to cAMP, a “second messenger” and key intracellular signaling molecule [ 40 ]. The AC of CyaA of Bordetellae [ 5 , 8 ], the edema factor (EF) of Bacillus anthracis [ 41 , 42 ] and the ExoY effector of Pseudomonas aeruginosa [ 43 , 44 ] play an important role in virulence of these pathogenic bacteria. These AC enzymes exhibit a very low catalytic activity inside bacterial cytosol and are only activated upon delivery into cytosol of host eukaryotic cells, where ExoY is activated by filamentous actin [ 45 ], while the EF and the AC domain of CyaA are activated upon binding of eukaryotic CaM in a 1:1 stoichiometry [ 22 , 41 , 46 ].…”
Section: Cyaa Structurementioning
confidence: 99%
“…Very recently, two groups independently demonstrated that ExoY activity can also lead to the inhibition of the host immune responses by suppressing the activation of TAK1 and decreasing the production of IL-1β (He et al, 2017;Jeon et al, 2017). The contribution of ExoY to P. aeruginosa virulence during acute and/or chronic infections were recently reviewed by T. Stevens and colleagues (Morrow et al, 2017). This mini-review summarizes some recent biochemical studies on ExoY and its regulation by actin.…”
Section: Introductionmentioning
confidence: 99%
“…ExoY is present in~90% of P. aeruginosa bacteria [12]. It was first described as a soluble adenylyl cyclase, generating cAMP within the cytosolic compartment.…”
Section: Introductionmentioning
confidence: 99%